Teorias da referência, ontologia e literatura - Almeida, Jones Alberto de (2010)
The objective of this thesis is clarify the concept of reference, in the context of the theories of meaning, as drawn up by the main theoretical analytical philosophy, and to evaluate the use of this concept in the work of critics and theoretical involved with the study and interpretation of texts in the literature. The option theoretical accept, reject, or a new meaning to the concept of reference, and by extension, the concepts of sense, truth, illusion, subjective, objective, cognitive, emotional, in the interpretation literary, served as a guide to submit the arguments and clarify some implications, mainly from the nature semantics, hermeneutics, logicals and ontologicals, involved in this debate. The search for a 'melting horizons', determined the dialogs that we have built up between the authors analyzed. This is an interdisciplinary study, an approach between the concepts of analytical philosophy and criticizes literary.